Neuroprotective Potential of Raloxifene via G-Protein-Coupled Estrogen Receptors in Aβ-Oligomer-Induced Neuronal Injury - Tetsuhito Nohara; Mayumi Tsuji; Tatsunori Oguchi; Yutaro Momma; Hideaki Ohashi; Miki Nagata; Naohito Ito; Ken Yamamoto; Hidetomo Murakami; Yuji Kiuchi (Biomedicines, 2023)
Amyloid-β (Aβ) is one of the causes of Alzheimer’s disease (AD), damaging nerve membranes and inducing neurotoxicity. AD is more prevalent in female patients than in male patients, and women are more susceptible to developing AD due to the decline in estrogen levels around menopause. Raloxifene, a selective estrogen receptor modulator, exhibits protective effects by activating the transmembrane G-protein-coupled estrogen receptor (GPER). Additionally, raloxifene prevents mild cognitive impairment and restores cognition. However, the influence of raloxifene via GPER on highly toxic Aβ-oligomers (Aβo)-induced neurotoxicity remains uncertain. In this study, we investigated the GPER-mediated neuroprotective effects of raloxifene against the neurotoxicity caused by Aβo-induced cytotoxicity. The impact of raloxifene on Aβo-induced cell damage was evaluated using measures such as cell viability, production of reactive oxygen species (ROS) and mitochondrial ROS, peroxidation of cell-membrane phospholipids, and changes in intracellular calcium ion concentration ([Ca2+]i) levels. Raloxifene hindered Aβo-induced oxidative stress and reduced excessive [Ca2+]i, resulting in improved cell viability. Furthermore, these effects of raloxifene were inhibited with pretreatment with a GPER antagonist. Our findings suggest that raloxifene safeguards against Aβo-induced neurotoxicity by modifying oxidative parameters and maintaining [Ca2+]i homeostasis. Raloxifene may prove effective in preventing and inhibiting the progression of AD.